The Kingdom of Keboklagan. [anthology].
The Kingdom of Keboklagan is a folk tale about that area that exaggerates and twists many functions of the land.
Found in: Philippine Folk Literature: The Epics. (GR 325 P48 2001 v.8)
Keywords: Literature-Collections.